2008
DOI: 10.1186/1475-2875-7-126
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of a new rapid diagnostic test, the First Response® Malaria Combo (pLDH/HRP2) card test, for malaria diagnosis in the forested belt of central India

Abstract: Background: Malaria presents a diagnostic challenge in tribal belt of central India where two Plasmodium species, Plasmodium falciparum and Plasmodium vivax, are prevalent. In these areas, rapid detection of the malaria parasites and early treatment of infection remain the most important goals of disease management. Therefore, the usefulness of a new rapid diagnostic (RDT), the First Response ® Combo Malaria Ag (pLDH/HRP2) card test was assessed for differential diagnosis between P. falciparum with other Plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
46
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 26 publications
7
46
0
Order By: Relevance
“…Bharti PK et al 13 had shown that rapid antigen testing for malaria was highly efficacious in comparison to microscopy. We had found similar result.…”
Section: Discussionmentioning
confidence: 99%
“…Bharti PK et al 13 had shown that rapid antigen testing for malaria was highly efficacious in comparison to microscopy. We had found similar result.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis was carried out at the community level by CHWs at health facilities, private clinics or health facilities run by non-government organizations (NGOs) or faith-based organizations. The study looked at all cases of malaria reported in the health facilities categorizing the data into i) clinically diagnosed malaria based on fever and other clinical signs; and ii) confirmed malaria diagnosis, either through microscopy or by RDT using the Malaria Ag P.f/Pan test (Standard Diagnostics, Yongin-si, Republic of Korea), a test for the Plasmodium falciparum histidine-rich protein II antigen and the Plasmodium lactate dehydrogenase constituent (Bharti et al, 2008;Keating et al 2009;Kamuliwo et al, 2013).…”
Section: Malaria Data and Managementmentioning
confidence: 99%
“…A revision of the treatment regimen for both uncomplicated and complicated malaria was released in 2014, adding artemether-lumefantrine (AL) to ACT as first line of treatment (NMCC, 2014) to be given within 24 hours of onset of symptoms. However, the use of rapid diagnostic tests (RDTs) was first initiated as a pilot project in some districts in 2005 to 2006 (Bharti et al, 2008) and was scaled up for country-wide use in 2008 (Keating et al, 2009). In 2009, Zambia began separate reporting for clinical and parasitological diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Although the authors acknowledged that their data can only be narrowly interpreted to indicate that heat stability can sometimes be a problem for tests, a number of subsequent authors have concluded that pLDH-based tests in general are inherently unstable in heat. 48,[50][51][52][53] Without delving into the cause of particular discrepancies, making general interpretations from comparative studies will be limited and confined to assessing one product over another. Although many studies of particular products conclude the that pLDH tests have greater specificity but equal or inferior sensitivity compared with HRP-2-based tests, 51,53,54 studies using different products have shown both superior sensitivity and specificity compared with popular HRP-2-based tests.…”
Section: The Practice Of Rdtsmentioning
confidence: 99%